O nacional e o popular em Xica da Silva de Carlos Diegues - Gomes, Hélton Santos (2020)
In this thesis we discuss issues that concern the “national” and the “popular” in Xica da Silva (1976), by Cacá Diegues in order to understand how the filmmaker worked with these concepts in the work mentioned. During the analytical path we tried to elucidate some of Diegues' ideas or proposals about cinematographic production at that time, mid 1970s. In the midst of the discussion of the central theme of this work, we addressed, from the reception of the work, issues that concern the situation of black men and women in Brazilian society and national cinema policy. In short, we seek to understand how the different readers / viewers placed themselves before the film narrative.